Comparison of Simulation and Experiment Results of Oil Film Temperature of the Connecting-Rod Big End Bearing in the Experimental Device - Pham, Trung Thien; Tran, Thi Thanh Hai; Luu, Trong Thuan (Old Journal, 2020)
The paper compares the simulation and experiment results of the lubricating oil temperature in the connecting-rod big end bearing. Simulating hydrodynamic lubrication for the connecting-rod big end bearing based on solving Reynolds equations, oil film thickness equations, load balancing equations and energy equations combined numerical lubrication simulation for the bearing by modeling thermal problems for oil films using finite element method. Experimental device and simulated rod made of elastic optical material are under the same load as that of a four-stroke engine. The temperature is measured by six thermocouple sensors located at positions 0°, 45°, 135°, 180°, 225°, 315° of the connecting-rod and at the middle section of the bearing along the length direction. The results from the research show the similarity between the simulation result and experience result. The temperature of the oil film in the connecting-rod big end bearing increases when the rotation speed increases and reaches the maximum value at the middle section of 360° angle of the crankshaft when there is an explosion. The higher viscosity the lubrication oil has, the higher temperature of the oil film it is in the connecting-rod big end bearing.